A critical analysis of the work-oriented curriculum based on John Dewey's philosophy - Agas, Gloria A. 1948- (1977)
This paper attempted at presenting an approach to rationalizing the work-oriented curriculum using some of John Dewey's philosophical theories on values, knowledge and reality. The curriculum's aims, methodology and content were looked through against the perspective of the theoretical trinity usually founding any educational structure, such as the WOC values, knowledge, and reality. Since the work-oriented curriculum is an activity program of studies, it may be said therefore that it does not go against the Deweyan naturalistic theory, and further therefore that it is strongly philosophically founded curriculum. It was concluded that the said curriculum is a recognition of man's nature, nature's nature, man's place in nature, and man-in-the-new-society's role in the betterment of his environment in the context of his realities.
Apendices: leaves 47-61.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita.
Keywords: Dewey, John -- 1859-1952; Work-oriented education -- Philippines; Education -- Philosophy; Education -- Curricula. -- Philippines